Contrasting Nutritional Acclimation of Sugar Maple (Acer saccharum Marsh.) and Red Maple (Acer rubrum L.) to Increasing Conifers and Soil Acidity as Demonstrated by Foliar Nutrient Balances - Collin, Alexandre; Messier, Christian; Côté, Benoît; Fontana, Mario; Bélanger, Nicolas (Frontiers in Ecology and Evolution, 2016)
Sugar maple (Acer saccharum Marshall, SM) is believed to be more sensitive to acidic and nutrient-poor soils associated with conifer-dominated stands than red maple (Acer rubrum L., RM). Greater foliar nutrient use efficiency (FNUE) of RM is likely the cause for this difference. In the context of climate change, this greater FNUE could be key in favouring northward migration of RM over SM. We used the concept of foliar nutrient balances to study the nutrition of SM and RM seedlings along an increasing gradient in forest floor acidity conditioned by increasing proportions of conifers (pH values ranging from 4.39 under hardwoods, to 4.29 under mixed hardwood-conifer stands and 4.05 under conifer-dominated stands). Nutrients were subjected to isometric log-ratio (ilr) transformation, which views the leaf as one closed system and considers interactions between nutrients. The ilr method eliminates numerical biases and weak statistical inferences based on raw or “operationally’’ log-transformed data. We analyzed foliar nutrients of SM and RM seedlings and found that the [Ca,Mg,K|P,N] and [Ca,Mg|K] balances of SM seedlings were significantly different among soil acidity levels, whereas they did not vary for RM seedlings. For SM seedlings, these differences among soil acidity levels were due to a significant decrease in foliar Ca and Mg concentrations with increasing forest floor acidity. Similar differences in foliar balances were also found between healthy and declining SM stands estimated from literature values. Conversely, foliar balances of RM seedlings did not differ among soil acidity levels, even though untransformed foliar nutrient concentrations were significantly different. This result highlights the importance of using ilr transformation, since it provides more sensitive results than standard testing of untransformed nutrient concentrations. The lower nutrient requirements of RM and its greater capacity to maintain nutrient equilibrium are factors that could explain its competitive success and recent northward expansion. This study underscores the importance of using nutrient balances to study the redistribution of plant species in natural ecosystems under climate change.